NUMBERED HEAD TOGETHER (NHT) TYPE COOPERATIVE LEARNING STRATEGY ON ECONOMICS LEARNING OUTCOMES ON ACCOUNTING MATERIAL - safira, Saskia; rijal, Abdul; sahade, Sahade (JURNAL EDUSCIENCE, 2024)
Abstract This study aims to determine the effect of cooperative learning strategies of the Numbered Head Together (NHT) type on the results of learning economics on accounting material for class XII IPS students at SMA Negeri 4 Soppeng. The variable in this study is the Numbered Head Together (NHT) cooperative learning strategy as the independent variable and learning outcomes as the dependent variable. The population of this study were all students of class XII IPS SMA Negeri 4 Soppeng. The sampling technique used the total sampling technique, samples from the population were obtained from the entire population with a sample of 50 students. Data collection techniques used are questionnaires, observation and documentation. The data analysis technique used is descriptive analysis of percentages, instrument testing and hypothesis testing.Based on the data analysis that has been done, there are five indicators of the Numbered Head Together NHT cooperative learning strategy, namely a) Estabilishing Set, b) Demonstrating, c) Guided Practice, d) Feedback, and e) Extended Practice where descriptive results are obtained at 70.70 % in the high category and learning outcomes of 89.6% which are classified as very high. The results of a simple linear regression analysis obtained the equation Y = 70.032 + 0.327X. This means that for every addition of one value of the NHT type cooperative learning strategy, there is an increase in learning outcomes of 0.327 units while the results of the coefficient of determination (r2) = 0.180 or 18%. Where NHT has a contribution to learning outcomes of 18%, the remaining 82% is influenced by other factors. Furthermore, from the results of the t-test analysis, it was obtained a significance value of alpha value of 0.000 <0.05, which means that NHT has a very significant effect on accounting learning outcomes, so the hypothesis is declared accepted. Keywords : Numbered Head Together (NHT) Learning, Learning Outcomes Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh strategi pembelajaran kooperatif tipe Numbered Head Together (NHT) terhadap hasil belajar ekonomi materi akuntansi siswa kelas XII IPS SMA Negeri 4 Soppeng. Variabel dalam penelitian ini adalah strategi pembelajaran kooperatif tipe Numbered Head Together (NHT)sebagai variabel bebas dan hasil belajar sebagai variabel terikat. Populasi dari penelitian ini adalah seluruh siswa kelas XII IPS SMA Negeri 4 Soppeng. Teknik pengambilan sampel menggunakan teknik total sampling, sampel dari populasi diperoleh dari seluruh jumlah populasi dengan sampel sebanyak 50 siswa. Teknik pengumpulan data yang digunakan adalah angket, observasi dan dokumentasi. Teknik analisis data yang digunakan adalah analisis deskriptif persentase, uji instrumen dan uji hipotesis. Berdasarkan analisis data yang telah dilakukan, terdapat lima indikator strategi pembelajaran kooperatif tipe Numbered Head Together NHT yaitu a) Estabilishing Set, b) Demonstrating, c) Guided Practice, d) Feedback, dan e) Extended Practice dimana diperoleh hasil deksriptif sebesar 70,70% dengan kategori tinggi dan hasil belajar sebesar 89,6% yang tergolong sangat tinggi. Hasil analisis regresi linear sederhana diperoleh persamaan  Y = 70,032 + 0,327X ini berarti setiap penambahan satu nilai strategi pembelajaran kooperatif tipe NHT, maka terjadi kenaikan pada hasil belajar sebesar 0,327 satuan sedangkan hasil koefisien determinasi (r2) = 0,180 atau 18%. Dimana NHT memiliki kontribusi terhadap hasil belajar sebesar 18% sisanya 82% dipengaruhi oleh faktor lain. Selnjutnya dari hasil analisis uji-t diperoleh nilai signifikansi nilai alpha sebesar 0,000 < 0,05 yang berarti NHT berpengaruh sangat signifikan terhadap hasil belajar akuntansi, sehingga hipotesis dinyatakan diterima.Kata kunci : Pembelajaran Numbered Head Together (NHT), Hasil Belajar